Programmable Logic Controllers (6th Edition) - Bolton W (Elsevier, 2015)
This textbook, now in its sixth edition, continues to be straightforward and easy-to-read, presenting the principles of PLCs while not tying itself to one manufacturer or another. Extensive examples and chapter ending problems utilize several popular PLCs, highlighting understanding of fundamentals that can be used regardless of manufacturer. This book will help you to understand the main design characteristics, internal architecture, and operating principles of PLCs, as well as Identify safety issues and methods for fault diagnosis, testing, and debugging. New to This edition: A new chapter 1 with a comparison of relay-controlled systems, microprocessor-controlled systems, and the programmable logic controller, a discussion of PLC hardware and architecture, examples from various PLC manufacturers, and coverage of security, the IEC programming standard, programming devices and manufacturer's software.